SPECTRAL REFLECTANCE OF IPÊ-AMARELO LEAVES UNDER DIFFERENT FORMS OF STORAGE AND COLLECTION TIME - Tramontina, Juliana; Käfer, Pâmela Suélen; Belloli, Tássia Fraga; Fontana, Denise Cybis (Floresta, 2019)
The application of spectroradiometry techniques to the study of tree species allows the acquisition of information related to plant physiology and morphology, which can be used in conjunction with orbital images. However, it is known that when a leaf is extracted the senescence process is started, which is characterized by cell constituents degradation, loss of water and modifications of the foliar mesophyll structure. In this context, this study aimed to evaluate the influence of the collection time and storage form on the spectral response of ipê-amarelo leaves. Thus, 32 leaves were collected in distinct times (1h, 2h, 24h and 48h) and conditioned with(C) and without(S) thermal storage. The data were evaluated from the visual analysis of the spectral curves, derivative analysis and statistical analysis. The experiment was conducted in a Randomized block design and data were submitted to analysis of variance (ANOVA) and Tukey test (p = 0.05). Results indicated that thermal storage might delay the senescence process of the leaves. Both the collection time and the storage form affect the pattern of spectral behavior of the leaves of ipê-amarelo. The collection time has not shown significant differences between 1-2h. The largest differences were found between 2-24h after collection.